Adrenocortical Tumors in Children With Constitutive Chromosome 11p15 Paternal Uniparental Disomy: Implications for Diagnosis and Treatment - Pinto, Emilia Modolo; Rodriguez-Galindo, Carlos; Lam, Catherine G.; Ruiz, Robert E.; Zambetti, Gerard P.; Ribeiro, Raul C. (Frontiers in Endocrinology, 2021)
ABSTRACT Pediatric adrenocortical tumors (ACTs) are rare and heterogeneous. Approximately 50% of children with ACT carry a germline TP53 variant, however, the genetic underpinning of remaining cases has not been elucidated. In patients having germline TP53 variants, loss of maternal chromosome 11 and duplication of the paternal copy (paternal uniparental disomy, [UPD]) occurs early in tumorigenesis and explains the overexpression of IGF2, the hallmark of pediatric ACT. Beckwith-Wiedemann syndrome (BWS) is also associated with overexpression of IGF2 due to disruption of the 11p15 loci, including segmental UPD. Here, we report six children with ACT, with wild type TP53, and germline paternal 11p15 UPD. Median age of five girls and one boy was 3.2 years (range 0.5-11 years). Two patients met the criteria for BWS before diagnosis of ACT. However, ACT was the first and only manifestation of paternal 11p15 UPD in four children. Tumor weight ranged from 21.5 g to 550 g. Despite poor prognostic features at presentation, such as pulmonary metastasis, bilateral adrenal involvement, and large tumors, all patients are alive 8-21 years after cancer diagnosis. Given the implications for management, we recommended that children with ACT and wild type TP53 be screened for germline abnormalities in chromosome 11p15.